2025 update to the Female Athlete Triad Coalition Consensus Statement part 1: State of the science and introduction of a new adolescent model - De Souza, M. J.; Williams, N. I.; Misra, M.; Nattiv, A.; Joy, E.; Barrack, M.; Ricker, E. A.; Gorrell, S.; Koltun, K. J.; O`Donnell, E.; Mallinson, R. J.; Salamunes, A. C. C.; et al. (Sports Medicine, 2026)
This paper is the first of two publications comprising a 2025 update to the 2014 Consensus Statement on treatment and return-to-play guidelines on the Female Athlete Triad (Triad), defined as three inter-related components including energy status, reproductive function, and bone health. The Triad is initiated by exposure to varying degrees of energy deficiency with or without disordered eating/eating disorders with primary pathological outcomes to the reproductive and skeletal systems. This first paper includes a detailed update on the scientific underpinnings of the Triad and introduces a new Triad model specific to the adolescent female athlete. Energy deficiency and "metabolic compensation" are added to the energy status continuum to describe adaptations that reflect energy conservation. Ovarian steroid hormone exposure and functional hypothalamic oligo-amenorrhea are added to the reproductive function continuum. Bone stress injury is added to the bone health continuum. Rates of change are depicted for the induction and recovery of clinical outcomes within the adult model. Evidence-based statements are presented throughout the paper and supported by a high number of level A and B grades.